METODE DEMONTRASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA POKOK BAHASAN SEMUA BERSIH HIDUP JADI NYAMAN - nurhayati, ai (Asaatidzah, 2023)
Education is always concerned with human development efforts, according to Tafsir A, (2013:33), that, "Humans need help so that they can succeed in becoming human beings. A person can be said to have become a human if he has human values ​​(traits). This shows that it is not easy to be human, which is why many people have failed to become human for a long time. So the aim of education is to humanize humans." The problem that occurs at SMPN 1 Sindangkerta class VII-5 is that the absorption capacity for PAI learning, especially in the application of material for making everything clean and comfortable, is very low, and the contributing factors are: Students don't know the purpose of studying the material, everything is clean, life is comfortable. The material presented was not well received by some students. There are some students who cannot practice ablution. This research aims to increase the learning motivation of class VII-5 students at SMPN 1 Sindangkerta on the subject of everything being clean, life is comfortable The demonstration method according to Syah (2000: 208) is a teaching method by demonstrating items, events, rules and the sequence of carrying out activities, either directly or through the use of teaching media that is relevant to the subject matter or material being presented. After using the demonstration method, the percentage of student activity in the overall cycle was 855.39%. The percentage of active students obtained was 85.54% belonging to the active category.